1996
DOI: 10.1016/s1078-5884(96)80168-7
|View full text |Cite
|
Sign up to set email alerts
|

Have the results of infrainguinal bypass improved with the widespread utilisation of postoperative surveillance?

Abstract: The patency of infrainguinal vein grafts would appear to be improved as a result of surveillance. However, no improvement in limb salvage has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 44 publications
0
32
0
2
Order By: Relevance
“…These stenoses may threaten the graft even if the patient is asymptomatic and the ABI is unchanged. Duplex ultrasound surveillance studies allow detection of these stenoses before graft thrombosis with greater sensitivity than evaluation by clinical history (limb ischemic symptoms), physical examination, or use of the resting ABI (155,(219)(220)(221)(222)(223)(224). Case series have indicated that revision of such asymptomatic stenoses improves long-term graft patency.…”
Section: Treadmill Exercisementioning
confidence: 99%
“…These stenoses may threaten the graft even if the patient is asymptomatic and the ABI is unchanged. Duplex ultrasound surveillance studies allow detection of these stenoses before graft thrombosis with greater sensitivity than evaluation by clinical history (limb ischemic symptoms), physical examination, or use of the resting ABI (155,(219)(220)(221)(222)(223)(224). Case series have indicated that revision of such asymptomatic stenoses improves long-term graft patency.…”
Section: Treadmill Exercisementioning
confidence: 99%
“…Overall, the trial has provided conclusive evidence of the suspicions raised by the summation analysis of Golledge et al 5 and the combined results of the 2 small RCTs that limb salvage is not improved by duplex surveillance. 31 The combined results of the previous small RCTs suggested that overall patency was worse in patients in the clinical follow-up arm rather than the duplex group; this trial has shown no statistically or clinically significant improvement in patency.…”
Section: Discussionmentioning
confidence: 72%
“…3,4 Duplex ultrasound scanning is currently the best method for detecting stenotic lesions that threaten graft patency during follow-up. 5 The correction of such lesions may improve graft patency and limb salvage rates. 6,7 However, to date, evidence to support this has been based largely on the findings of smaller-scale observational studies, 8 -11 in the absence of a large multicenter, randomized, controlled trial (RCT).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Por ello, no existe actualmente unanimidad en la aplicación de un programa de seguimiento estricto con eco-doppler de estos pacientes (43,66,(161)(162)(163)(164)(165) .…”
Section: Protocolos De Seguimiento En Cirugía Vascularunclassified